ACL Reconstruction: Problems, History and Future. Part 1 - Zazirnyi, I.M.; Kostrub, O.O. (TERRA ORTHOPAEDICA, 2020)
Summary. Damage to the anterior cruciate ligament (ACL) of the knee joint is a common injury in sports medicine. Before advances in arthroscopy and surgical techniques, an ACL damage was considered a career ending injury for many athletes. Since the 1990s, there has been a rapid development of arthroscopic surgery for ACL and continuous improvement of these techniques. Today’s athletes can expect a pre-injury level of stability and function after an ACL reconstruction. Modern surgical interventions have come a long way, having studied both the successes and failures of previous surgical techniques. In the United States, an ACL damage is diagnosed annually from 100,000 to 200,000 cases, making this the most common ligament injury [9, 10]. This number continues to increase in both the general population and in individuals who play sports. Football players sustain the greatest number of ACL injuries (53% of the total), with skiers and gymnasts also at high risk. The history of ACL reconstruction can be traced as far back as the Egyptians times. Research and innovation are constantly evolving, and this leads to improved clinical results. The knowledge of the evolution of ACL reconstruction is invaluable to those who continue to try to improve the outcomes of the procedure and reduce the risks of repeating mistakes of the past.